Sex difference in the relationship between childhood obesity and abnormal lipid profiles in young adults - Keyang Zheng; Yinkun Yan; Linlin Ma; Rufei Liu; Tianzhu Zhao; Yuxuan Wei; Zixu Zhao; Hong Cheng; Dongqing Hou; Junting Liu; Xiaoyuan Zhao; Wenli Cheng; et al. (BMC Endocrine Disorders)
Abstract Background Abnormal lipid profiles are a major risk factor for cardiovascular diseases, and childhood obesity has been linked to changes in lipid metabolism in adults. However, the relationship between childhood obesity and adult lipid profiles, as well as the potential sex differences, remain unclear. This study aimed to examine the association between childhood obesity and abnormal lipid metabolism in young adults, specifically focusing on sex differences. Methods Data were obtained from the Beijing Blood Pressure Cohort Study, which included 1220 participants aged 28–45 years. Childhood obesity was defined based on body mass index (BMI) and subscapular skinfold thickness (SSFT) measurements. Adult lipid profiles, including triglycerides (TG), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), and total cholesterol (TC), were measured. Logistic regression models were used to assess the association between childhood obesity and adult lipid profiles, adjusting for potential confounders. Results During the follow-up period, 18 (2.9%) of 617 male subjects with normal weight as children were obese as adults. Of 516 female subjects with normal weight as children, 9 (1.7%) were obese as adults. In males, childhood overweight/obesity was positively associated with high TG in adulthood (OR = 1.72, 95%CI 1.03–2.85). In females, childhood overweight/obesity was significantly associated with high TC (OR = 5.96, 95%CI 1.42-25.00) and high LDL-c (OR = 6.91, 95%CI 1.17–40.75) in adulthood. The analysis of change in adiposity status from childhood to adulthood revealed that males with normal childhood weight and adult obesity could have the highest risk of all lipid disorders. In females, those with childhood obesity and normal adult weight seemed to have the highest risk of hypercholesterolemia and high TC. Conclusion This study demonstrates a sex difference in the relationship between childhood obesity and abnormal lipid profiles in young adults. Childhood overweight/obesity is associated with adverse lipid profiles in adulthood, with different patterns observed in males and females. These findings highlight the importance of early intervention and prevention strategies for childhood obesity to mitigate the risk of future cardiovascular diseases.